Pengaruh Analisis Harga Saham terhadap Arus Kas, Pertumbuhan Penjualan, dan Laba Bersih terhadap Kinerja Perusahaan: Studi Survei Pada Perusahaan Pertambangan Batubara yang Terdaftar di Bursa Efek Indonesia - Dean Subhan Saleh; Asep Saepudin; Surtikanti Surtikanti; Sri Dewi Anggadini (Society, 2022)
This study focuses on cash flow, sales growth and net income as the main aspects investigated to determine how the three aspects impact stock prices within the studied companies. Based on this point, this paper sought to determine the impact of cash flow, sales growth, and net profit on stock prices in the Coal Mining Companies listed on Indonesia’s Stock Exchange from 2012 to 2017. The study used an analytical method, applying a descriptive analysis approach to verify the results. The population in this study were five coal mining companies listed on the Indonesian Stock Exchange from a list of those considered real coal mining companies. The data considered was for six years, ranging from 2012 to 2017. The sample used was purposive sampling, considering certain criteria required to establish an appropriate sample for the study. The authors later used the analytical method of multiple linear regression for data analysis. The results of hypothesis testing in this study indicate that: changes in cash flow have a significant positive effect on stock prices, changes in sales growth have a significant positive influence on stock prices, and changes in net income have a significant positive effect on the stock price in the coal mining companies listed on the Indonesian Stock Exchange.